2011
DOI: 10.1186/1447-056x-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Treat-to-target approach in managing modifiable risk factors of patients with coronary heart disease in primary care in Singapore: what are the issues?

Abstract: BackgroundThe key management strategy for established coronary heart disease (CHD) patients is to control the underlying risk factors. Further complications will be reduced when these risk factors are treated-to-target (TTT) as recommended by clinical practice guidelines. These targets include blood pressure (BP) lower than 130/80 mm Hg and LDL-cholesterol of less than 2.6 mmol/L and for those with type 2 diabetes mellitus (DM), HBA1c less than 7%. This article aimed to explore the issues affecting this approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…From these 33 miRNA, miRNAs were selected for further analysis based on following criteria: (1) at least 5-fold up-regulated in patients as compared with controls, (2) a P <0.01 was considered statistically significant in patients as compared with controls and (3) the bioinformatic analysis revealed the potential target genes for the identified miRNAs and these target genes might be involved in the onset and development of CAD [ 21 23 ]. Two miRNAs were showed a significant differential expression between CAD patients and controls.…”
Section: Resultsmentioning
confidence: 99%
“…From these 33 miRNA, miRNAs were selected for further analysis based on following criteria: (1) at least 5-fold up-regulated in patients as compared with controls, (2) a P <0.01 was considered statistically significant in patients as compared with controls and (3) the bioinformatic analysis revealed the potential target genes for the identified miRNAs and these target genes might be involved in the onset and development of CAD [ 21 23 ]. Two miRNAs were showed a significant differential expression between CAD patients and controls.…”
Section: Resultsmentioning
confidence: 99%
“… 27 A study in Singapore found that >80% of CAD patients did not know their LDL-C target because of poor, or lack of, communication regarding LDL-C targets between physicians and patients, suggesting that patients may not achieve their treatment targets. 34 Besides, many studies show a positive relationship between adherence to taking statins and achieving the LDL-C goal. 35 37 However, adherence to statin therapy declines over time; ACS patients had a 2-year adherence rate with statins of about 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Preventive measures should be the first and best choice in this case, such as the prevention of direct contact of blood or blood-derived products from the infected patients and infected vectors from the infected host [ 105 ]. Daytime is the most suitable time for biting Aedes mosquitoes; consequently, its contact can be diminished or avoided using the following techniques: By using nets (e.g., insecticide-treated nets) and mosquito repellents (e.g., coils, solids (sticks), aerosols, liquids, pump sprays, and nonsticky creams) By wearing gloves and other defensive clothing Through well-planed management of wastes and stored water By destroying the mature Aedes mosquitoes or larvae through applying some protective chemicals (e.g., N,N-Diethyl-3-Methylbenzamide, diethyl carbonate, metofluthrin, oil of lemon-eucalyptus, diethyl phthalate, ethyl hexanediol, and picaridin) [ 106 , 107 ]. …”
Section: Control Of Denv and Its Vectorsmentioning
confidence: 99%
“…By destroying the mature Aedes mosquitoes or larvae through applying some protective chemicals (e.g., N,N-Diethyl-3-Methylbenzamide, diethyl carbonate, metofluthrin, oil of lemon-eucalyptus, diethyl phthalate, ethyl hexanediol, and picaridin) [ 106 , 107 ].…”
Section: Control Of Denv and Its Vectorsmentioning
confidence: 99%
See 1 more Smart Citation